Precedents and case-based reasoning in the European Court of Justice : unfinished business / Marc Jacob. - Jacob, Marc A., 1979- (Cambridge University Press, 2014)
Past cases are the European Court of Justice's most prominent tool in making and justifying the rulings and decisions which affect the everyday lives of more than half a billion people. Marc Jacob's detailed analysis of the use of precedents and case-based reasoning in the Court uses methods such as doctrinal scholarship, empirical research, institutional analysis, comparative law and legal theory in order to unravel and critique the how and why of the Court's precedent technique. In doing so, he moves the wider debate beyond received 'common law' versus 'civil law' figments and 'Eurosceptic' versus 'Euromantic' battle lines, and also provides a useful blueprint for assessing and comparing the case law practices of other dispute resolution bodies.